Preclinical evaluation of safety and potential of black hellebore extracts for cancer treatment - Jennifer E. Felenda; Claudia Turek; Nora Mörbt; Anja Herrick; Margit B. Müller; Florian C. Stintzing (BMC, 2019)
Abstract Background The therapeutic use of Helleborus niger L. is manifold due to its specific phytochemical composition. Two compound groups, the ranunculin derivates including protoanemonin and the steroidal saponins, are also associated with toxicity (genotoxicity, disintegration of membrane structures). Therefore, in vitro investigations were performed on safety aspects of a Helleborus niger aqueous fermented extract (HNE). In addition its therapeutic potential against various cancer cell lines was assessed to gain insight into the respective mechanisms of action. Methods To evaluate the safe use of HNE, Ames and hemolytic tests were carried out. Two angiogenesis assays in 2D and 3D design were conducted to assess the anti-angiogenetic potential, for which human umbilical vein endothelial cells (HUVEC) were chosen. A panel of tumor cell lines was used in 2D and 3D proliferation assays as well in the migration- and invasion-assay. All investigations were performed with HNE compared to reference substances. The 2D proliferation assay was additionally performed with isolated compounds of HNE (characteristic steroidal saponins). Results HNE did not exhibit any genotoxic potential. Concentrations up to 10 μl/ml were classified as non-hemolytic. HNE exerted anti-angiogenetic effects in HUVEC and anti-proliferative effects in five cancer cell lines, whereas hellebosaponin A and D as well macranthosid I did not show comparable effects neither singly nor in combination. Due to the inherent instability of protoanemonin in isolated form, parallel investigations with protoanemonin could not be performed. HNE (600-1000 μg/ml) inhibited the migration of certain cancer cells by > 80% such as Caki-2, DLD-1 and SK-N-SH. Conclusion HNE exhibit neither genotoxic nor hemolytic potential. The present investigations verify the anti-angiogenetic effects on HUVEC, the anti-proliferative effects and migration-inhibiting properties on tumor cells. The lower effect of the relevant steroidal saponins compared to the whole extract underlines the fact that the latter is more effective than a blend of isolated pharmacologically active components.